Abdominoplasty-Related Nerve Injuries: Systematic Review and Treatment Options. (February 2014) - Ducic, Ivica; Zakaria, Hesham M.; Felder, John M.; Arnspiger, Sarah
Background: Abdominoplasty is a common cosmetic procedure; nerve injury is an underexplored risk of the procedure. Objective: The authors review existing literature to examine the incidence and treatment of nerve injuries after abdominoplasty procedures and provide a treatment algorithm based on their results. Methods: A search of the literature on MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews was undertaken. After full-text review, 23 articles met our criteria. Any mentions of nerve injury, including references to a lack of nerve injury, were documented. All data were pooled for analysis. From our combined data, we calculated the risks of postabdominoplasty nerve injury by dividing the total number of nerve injuries by the total number of patients. Results: Pooled data showed that 1.94% of patients sustained specific nerve injury, and 1.02% of patients sustained permanent injury after abdominoplasty. In addition, 7.67% experienced decreased sensation, 1.07% reported chronic pain, and 0.44% reported temporary weakness or paralysis. Nerves directly injured were the lateral femoral cutaneous (1.36% of patients) and iliohypogastric (0.10%) nerves. Nerves injured from surgical positioning were the brachial plexus (0.10%), musculocutaneous (0.10%), radial (0.05%), sciatic (0.19%), and common peroneal (0.05%) nerves. Conclusions: Although our results showed a low incidence of postabdominoplasty nerve injury, the lasting impact on affected patients' quality of life can be significant. Appropriate and timely treatment by a multidisciplinary team is critical to optimize patient outcomes. Better reporting of nerve injuries in future studies of abdominoplasty will provide more accurate information about the incidence and consequences of these injuries. Level of Evidence: 4